Experimental investigation on noise and vibrations of biodiesel-butanol blends for diesel engine. Issue 1 (February 2021) - Erdiwansyah,; Sani, M.S.M.; Mahidin,; Zaki, M.; Kadarohman, Asep; Muhibbuddin,; Sardjono, R.E; Gani, Asri
Abstract: Diesel engines have extensively used several developing countries to produce electricity. This is done in various sizes, small and medium, which are driven by millions of diesel engine generators. These engines or generators produce vibrations and noisy and pollute the air. Thus, an alternative to diesel is needed for such applications. Turpentine-diesel fuel mixture is one such alternative. However, there have not many efforts made so far to evaluate noise and vibration characteristics. This study is done to try filling the gap and comprehensively investigate the use of Turpentine-diesel mixed fuels. This experiment uses a single-cylinder-4- stroke diesel engine operated at different rpm speeds and engine loads. Detailed measurements are made for engine noise and vibration. This measurement is used to connect the reciprocity of engine noise and vibration. The relationship of chemical parameters and physical properties to the tested fuel explored. The test results using turpentine-diesel fuel show the vibration and noise characteristics better for the upper-middle load. The correlation between noise and vibration characteristics of the test fuel has a strong relationship. This study has provided a detailed phenomenological explanation of the nature of the fuel. Finally, turpentine blends are a viable alternative to diesel fuel, especially in diesel engines